Localized and Systemic Inflammatory Mediators in a Murine Acute Mastitis Model - Takashima M (Dove Medical Press, 2021)
Miyuki Takashima,1,2 Christian Lalonde,1 Laura Ashley Olszanski,1 Feng-Qi Zhao1 1Department of Animal and Veterinary Sciences, University of Vermont, Burlington, VT, 05405, USA; 2Wakunaga Pharmaceutical Co. Ltd, Osaka, 532-0003, JapanCorrespondence: Feng-Qi Zhao Email fzhao@uvm.eduIntroduction: Milk depression is the major driver of economic loss due to mastitis in dairy animals. The aim of this study was to identify potential mediators of milk depression by investigating the local and systemic changes in gene expression or cytokine production during endotoxin challenge of the mammary gland in a mouse model.Methods: The left and right sides of the 4th pair of mouse mammary glands were alternatively injected with either lipopolysaccharide (LPS, Escherichia coli 055: B5, 50 μL of 0.4 mg/mL) or sterile PBS through the teat meatus 3 days postpartum (n = 9). The 4th glands were individually collected 12 h after LPS injection and analyzed to identify gene expression changes by RNA sequencing and real-time PCR, and the plasma was collected before and after LPS challenge and analyzed to determine the levels of 32 cytokines.Results: Transcriptome analysis showed that in addition to strong pro-inflammatory responses, which included granulocyte and monocyte migration and cytokine production and signaling, the LPS-treated glands exhibited strong ubiquitin-mediated and immune-mediated proteasome activation and an increase in nitric oxide-mediated oxidative stress. Furthermore, LPS induced a down-regulation in vesicle membrane, vesicle-mediated trafficking, and metabolic processes of amino acids and other organic molecules in the mammary gland. Of the 32 cytokines analyzed, the levels of 24 (mainly IL-6, G-CSF, MCP-1, RANTES, MIG, MIP-1b, KC, MIP-2, IP-10, and TNFα) were increased or tended to increase in the blood after LPS treatment, and only the levels of IL-9 were decreased. In the mammary gland after LPS challenge, the levels of IL-5, IL-6, IP-10, LIF, MCP-1, MIP-2, and TNFα were significantly increased, and the levels of INF&Ugr;, IL-2, IL-4, IL-10, and IL-12 (p40) were decreased.Discussion: These observations provide potential markers and targets for further studies on the prevention and treatment of gram-negative bacteria-induced mastitis.Keywords: cytokine, lipopolysaccharide, oxidative stress, proteasome, transcriptome change